Competitive environment problems and challenges in the pre-pandemic and post-pandemic society - George Abuselidze; Gia Zoidze (Economic Themes, 2023)
Competition and a competitive environment serve as a crucial foundation for the effective use of resources and the growth of economy, pushing enterprises to be more efficient, limit costs, and spend more in inventing and developing new goods. Customers may obtain more advantages at a lesser cost and of better quality when there is a strong competition. The competitive climate makes the state more appealing to investors, increasing the possibility of attracting local or international investment. Consumer protection and competition are critical for achieving economic growth and decreasing poverty. The jurisdiction and economic environment in which a enterprise works have a considerable impact on the quality of competition. The goal of the state and associated institutions is to encourage competition and to avoid any activities that place market participants and consumers in an unfair situation. It is also critical that the state's activities and appropriate regulatory standards do not impose a significant burden on the business sector, since both business and consumer rights must be respected.
Keywords: D22; D23; L1; L2; 330; competition; competitive environment; antitrust regulation; economic growth; society